Level 2 clinical supervision for community practitioners working with palliative and end-of-life care patients. (26th January 2023) - Kingsley, Marc J; Hussain, Feryad; Ma, Rumin
Abstract : Background: Little has been written on the availability of specialist level 2 supervision groups to support community practitioners regarding the emotional components of their palliative and end-of-life caseload. Adapted level 2 groups (AL2Gs) have been piloted in three community teams in the NHS to address this. Aims: This study aimed to evaluate whether access to AL2Gs benefited community palliative and end-of-life practitioners at three sites. The outcomes for those who attended and those unable to attend were considered. Findings: Attendees found AL2Gs beneficial, reporting better confidence and wellbeing, plus a sense of containment through group cohesion and trust in the facilitators and fellow AL2G members. Most would recommend the groups to all staff working in community palliative care. Practitioners who were not able to attend relied on informal and ad-hoc peer support, and had concerns about their skills in managing patients' psychological needs. Conclusion: Community nurses benefit from attending AL2Gs to support them with their palliative care/end-of-life caseloads. It is recommended that all community staff involved in this type of care have access to regular clinical supervision, especially in a group format.